Separation of galactoglucomannans, lignin, and lignin-carbohydrate complexes from hot-water-extracted Norway spruce by cross-flow filtration and adsorption chromatography - Niklas Westerberg; Hampus Sunner; Mikaela Helander; Gunnar Henriksson; Martin Lawoko; Anders Rasmuson (BioResources, 2012)
A simple method to simultaneously recover polymeric carbohydrates, mainly galactoglucomannans (GGM), lignin, and lignin-carbohydrate complex (LCC) from hot-water-extracted Norway spruce wood is presented. The isolation method consists of cross-flow filtration, where high and low molecular mass species are removed, followed by fixed-bed adsorption on a hydrophobic polymeric resin (XAD-16) to remove lignins and lignans. In the second step of fixed-bed adsorption, a phenylic reversed-phase analytical chromatography column, where mass transport resistance is minimized and a very high selectivity towards aromatic compounds have been observed, was used to separate LCC from GGM. The isolated LCC fraction contained about 10% aromatics, whereas the upgraded GGM fraction contained about 1.5% aromatics and the lignin fraction contained about 56% aromatics. Polymeric xylan was accumulated in the GGM fraction, while mannose was the dominant sugar found in the LCC fraction. As products, approximately 7% was recovered in the lignin fraction in the first adsorptive step, 5% was recovered as LCC, and 88% as upgraded hemicelluloses.